Practice effects in cognitive assessments three years later in non-carriers but not in symptom-free mutation carriers of autosomal-dominant Alzheimer's disease: Exemplifying procedural learning and memory? - Almkvist, Ove; Graff, Caroline (Frontiers in Aging Neuroscience, 2022)
Practice effects (PEs) defined as an improvement of performance in cognition due to repeated assessments between sessions are well known in unimpaired individuals, while less is known about impaired cognition and particularly in latent brain disease as autosomal-dominant Alzheimer's disease. The purpose was to evaluate the general (across tests/domains) and domain-specific PE calculated as the annual rate of change (ARC) in relation to years to the estimated disease onset (YECO) and in four groups of AD: asymptomatic mutation carriers (aAD, n = 19), prodromal, i.e., symptomatic mutation carriers, criteria for AD diagnosis not fulfilled (pAD, n = 4) and mutation carriers diagnosed with AD (dAD, n = 6) as well as mutation non-carriers from the AD families serving as a healthy comparison group (HC, n = 35). Cognition was assessed at baseline and follow-up about 3 years later by 12 tests covering six domains. The aAD and HC groups were comparable at baseline in demographic characteristics (age, gender, and education), when they were in their early forties, while the pAD and dAD groups were older and cognitively impaired. The results on mean ARC for the four groups were significantly different, small, positive, and age-insensitive in the HC group, while ARC was negative and declined with time/disease advancement in AD. The differences between HC and aAD groups in mean ARC and domain-specific ARC were not significant, indicating a subtle PE in aAD in the early preclinical stage of AD. In the symptomatic stages of AD, there was no PE probably due to cognitive disease-related progression. PEs were the largest in the verbal domain in both the HC and aAD groups, indicating a relationship with cognitive vulnerability. The group-related difference in mean ARC was predominant in timekeeping tests. To conclude, the practice effect in over 3 years was suggested to be linked to procedural learning and memory.